The diversity of yeasts associated with grapes and musts of the Strekov winegrowing region, Slovakia - Nemcová, Kornélia; Breierová, Emília; Vadkertiová, Renáta; Molnárová, Jana (Folia microbiologica, 2015)
Many different yeast species have been isolated from grapes and musts worldwide. The diversity and frequency of yeasts depend on a number of factors such as the grape variety, the physical damage of the grapes, the weather conditions and the chemical composition of must. A total of 366 isolates were associated with the three grape cultivars: Blue Frankish, Green Veltliner and Sauvignon blanc over four consecutive years. Yeast cultures were isolated from the grapes and from the fermenting musts after the first and seventh days. The ascomycetous yeasts of the genera Aureobasidium, Candida, Hanseniaspora, Metschnikowia, Pichia, Saccharomyces and Saccharomycopsis together with basidiomycetous yeasts of the genera Cryptococcus, Dioszegia, Filobasidium, Rhodotorula and Sporidiobolus were associated with the three grape varieties. Hanseniaspora uvarum, Metschnikowia pulcherrima, Pichia kluyveri, Pichia kudriavzevii and Sporidiobolus pararoseus were found on the berries in significant amounts. P. kluyveri and P. kudriavzevii were more associated with the damaged grapes, whereas Sp. pararoseus with intact ones. H. uvarum and M. pulcherrima were present on both types of grapes almost equally. The yeast composition and quantitative representation of yeast species varied over the grape varieties and the years examined. Although the basidiomycetous species formed a significant proportion of the yeast population in some individual grape variety/year combinations, the ascomycetous species were dominant.
Keywords: biodiverzita; ribozomální DNA; RNA ribozomální; Genes, rRNA; DNA, Ribosomal; houby; Wine; fungální RNA; Slovakia; DNA, Fungal; Phylogeny; Fungi; RNA, Ribosomal; Biodiversity; RNA, Fungal; Sequence Analysis, DNA; DNA fungální; geny rRNA; Slovenská republika; sekvenční analýza DNA; Vitis; fylogeneze; víno